The Impact of a Procurement Implementation and Government Internal Control System on Goods/Services Procurement Fraud Prevention by Using Organization Ethical Culture as a Moderating Variable - Arasy Ghazali Akbar (Jurnal Economia, 2019)
Abstract                                                                                     This study aims to empirically examine and prove the organization's ethical culture moderating impact on the relationship between e-procurement implementation and the government's internal control system with fraud prevention in procuring goods and services. Based on the purposive sampling method, 55 obtained samples were analyzed by using moderated regression analysis. The results show several findings, first, implementation of e-procurement has a significant effect on fraud prevention. Second, the government's internal control system has a significant effect on fraud prevention. The third and fourth findings indicate that the organization ethical culture is supported as a moderating variable. Keywords: e-procurement, government’s internal control system, organization ethical culture, fraud preventionPengaruh Implementasi E-Procurement dan Sistem Pengendalian Internal Pemerintah terhadap Pencegahan Fraud Pengadaan Barang/Jasa dengan Budaya Etis Organisasi sebagai PemoderasiAbstrakPenelitian ini bertujuan untuk menguji dan membuktikan secara empiris efek moderasi budaya etis organisasi terhadap hubungan implementasi e-procurement dan sistem pengendalian internal pemerintah dengan pencegahan fraud pengadaan barang dan jasa. Berdasarkan metode purposive sampling diperoleh 10 sampel OPD yang dianalisis dengan menggunakan moderated regression analysis. Hasil menunjukkan beberapa temuan, pertama implementasi e-procurement berpengaruh terhadap pencegahan fraud. Kedua, sistem pengendalian internal pemerintah berpengaruh terhadap pencegahan fraud. Temuan ketiga dan keempat menunjukkan bahwa budaya etis organisasi terdukung sebagai variabel moderasi. Kata Kunci: e-procurement, sistem pengendalian internal pemerintah, budaya etis organisasi, pencegahan fraud.